Estabelecimento e caracterização morfológica de esferoides derivados da linhagem celular de hepatocarcinoma humano (Hep-G2) - Barrios, Nathália Liz (Universidade Federal de São Carlos, 2025)
Cell culture in the 3D model morphologically and physiologically mimics the conditions found in vivo, making the results obtained from therapies regarding toxicity, resistance, and barriers more reliable. Additionally, 3D culture emerges as a promising tool to help reduce the use of animals in scientific research. In this context, using the liquid overlay methodology, we tested the formation of spheroids from human hepatocarcinoma cells (HepG-2). This methodology proved promising when 1% agarose was used as a non-adhesive substrate, as it led to the formation of compact and well-organized spheroids, with diameters ranging from 300 to 141 μm. Moreover, this method was found to be easy to handle and cost-effective. Due to the particular morphological organization of spheroids, conventional cell viability assays used for monolayer cultures were unsuitable for this purpose, requiring adaptations to other spheroid characterization methods, such as histological techniques. Regarding the ability to uptake nanoparticles, the spheroids showed promising results, with nanoparticle internalization observed under all tested cell density conditions and spheroid age. However, a more detailed characterization, especially of the spheroid core, must be conducted to establish and standardize a reproducible protocol for spheroid formation, including for cell lines other than HepG-2. So, this study contributed to advancing the modeling of in vitro systems that better represent the tumor microenvironment, offering a platform that, with further characterization, could be promising for drug screening and toxicological testing.
Establishment and morphological characterization of spheroids derived from the human hepatocarcinoma cell line (Hep-G2)
Keywords: Cultura 3D; Esferoides; Sobreposição líquida; ENGENHARIAS::ENGENHARIA BIOMEDICA::BIOENGENHARIA